Implementation of the Population Alert School (SSK) Program at SMPN 2 Nganjuk - Amelya Dwi Irianti; Vidya Imanuari Pertiwi (Sean Institute, 2026)
Early marriage and bullying remain serious challenges to human resource development in Indonesia. In response, the National Population and Family Planning Board (BKKBN) initiated the Population-Aware School Program (Sekolah Siaga Kependudukan or SSK). This study aims to analyze the implementation of the SSK Program at SMPN 2 Nganjuk based on Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure, to determine its effectiveness. A descriptive qualitative approach was employed using purposive sampling. Data were collected through in-depth interviews, direct observation, and documentary studies, with validity tested through source and method triangulation.